A European collaborative study of cyclophosphamide, bortezomib, and dexamethasone in upfront treatment of systemic AL amyloidosis - Palladini, Giovanni; Sachchithanantham, Sajitha; Milani, Paolo; Gillmore, Julian; Foli, Andrea; Lachmann, Helen; Basset, Marco; Hawkins, Philip; Merlini, Giampaolo; Wechalekar, Ashutosh D. (Blood, 2015)
The combination of cyclophosphamide/bortezomib/dexamethasone (CyBorD) showed early promise of high rates of hematologic responses tempered by studies showing the inability to overcome poor prognosis of advanced cardiac amyloidosis. Large studies are needed to clarify its role in light chain (AL) amyloidosis. We report the outcome of 230 patients treated frontline with CyBorD. Overall hematologic response rate was 60–, and in the 201 patients with measurable disease it was 62–, with 43– achieving at least very good partial response (VGPR). Cardiac response was reached in 17– of patients and renal response in 25– of patients. Advanced cardiac stage III patients (amino-terminal pro-natriuretic peptide type B >8500 ng/L) had lower response rates (42–, ≥ VGPR 23–) and poorer survival (median, 7 months). Nevertheless, hematologic response improved survival in these subjects (67– at 2 years), showing the importance of striving for a good response even in this group. •CyBorD achieves excellent outcome in noncardiac patients with AL amyloidosis and can rescue subjects with reversible heart damage.•The outcome of high-risk patients remains poor, but response to CyBorD can also improve survival in this group.